Biased Arbitrators and Tribunal Decisions Against Developing Countries: Stylized Facts on Investor‐State Dispute Settlement. (12th May 2017) - Nunnenkamp, Peter
Abstract: Based on UNCTAD's database on investor‐state dispute settlements (ISDS), we find that many cases raised against developing countries are handled by fairly unbiased tribunals. As for ISDS outcomes, the overall ratio of investor wins over state wins is below one. Nevertheless, it is harder for developing countries, compared to high‐income countries, to achieve state wins in international arbitration of investment disputes. Copyright © 2017 John Wiley & Sons, Ltd.